(untitled) - Deutsche Vereinigung für Parlamentsfragen; Chefredaktion: Prof. Dr. Suzanne S. Schüttemeyer, Martin-Luther-Universität Halle-Wittenberg; Mitglieder der Redaktion: Prof. Dr. Jörg-Detlef Kühne, Leibniz Universität Hannover; Prof. Dr. Werner J. Patzelt, Technische Universität Dresden; Thomas Hadamek, Ministerialrat, Verwaltung des Deutschen Bundestages, Berlin; Prof. Dr. Sven T. Siefken, Hochschule des Bundes für öffentliche Verwaltung. Beauftragter des Vorstands der DVParl: Prof. Dr. Heinrich Oberreuter, Universität Passau. Gründer der Zeitschrift: Winfried Steffani† und Uwe Thaysen † (ZParl Zeitschrift für Parlamentsfragen, 2022)
Zeitschrift für Parlamentsfragen contains articles on political issues dealing with representation and legitimation of the political system. The articles provide a broad overview of the functioning of national and regional parliaments as well as a forum for comparative analysis of international parliaments. One stress is on the parliamentary development of different countries. Indices are provided in every issue which makes the ZParl an outstanding reference book for institutional and comparative political studies. Website: www.zparl.nomos.de